Antioxidant Potential of ulva rigida c. Agardh Extract: Protection from Oxidative Stress Hypothyroidism - S. TAŞ (International Journal of Secondary Metabolite)
The purpose of this study was to evaluate the effects of Ulva rigida C. Agardh, one of the green algae, on and antioxidative system in the propylthiouracil (PTU)-induced hypothyroid rats. Thirty-two rats randomly divided into four groups: control (C), control+U. rigida extract (C+UR), hypothyroid (H) and hypothyroid+U. rigida extract (H+UR). U. rigida (2%) was administered in drinking water for 5 weeks after the induction of hypothyroidism. Hypothyroid rats were under oxidative stress as reflected by icreased plasma and tissue malondialdehyde (MDA) levels. U. rigida reduced serum total cholesterol and,- triglyceride levels and plasma and heart skeletal muscle, liver and,- kidney tissue MDA levels in the H+UR group. Serum total cholesterol and tissues MDA levels were reduced in the C+UR group. Whole blood glutathione peroxidase and erythrocyte superoxide dismutase activities were increased in the H+UR and C+UR groups compared with those of te respective control groups. Paraoxonase and arylesterase activities were lower in the H group and U. rigida increased paraoxonase and arylesterase activities in C+UR and H+UR groups. We conclude that hypothyroidism is associated with oxidative stress and, U. rigida extract might have a potential use as a protective antioxidant agent in hypothroidism.